Medida de conformidade para o ISSQN: uma análise de fronteira estocástica para o Município de Fortaleza no exercício de 2022 - Carneiro, Marcelo Sobreira (2024)
The present work aims to create, based on objective criteria, a compliance metric for the Tax on Services of Any Nature (ISSQN). The choice of ISSQN is due to its significance in the revenue collection of the municipality of Fortaleza. Over the past 11 years, it has represented more than 44% of the tax revenue collected every year. To establish this metric, the stochastic frontier model was used t he use of stochastic frontier allows capturing non systematic variations in service product ion, enabling a more robust analysis. The distance from the frontier allows identifying the most and least efficient producers. This measure of technical efficiency is the compliance metric. The data used are from the Finance Department of Fortaleza SEFIN and the Municipal Secretariat of Economic Development SDE. The collected information included service revenue, total ISSQN issued, total invoices issued, total area of the enterprise, identification of the service list item, and option for the National Simples regime for the year 2022, in addition to the last Human Development Index HDI e Human Development Income Index IDHR of the neighborhoods of the municipality of Fortaleza. The best index was obtained by the Port, airport, railway, bus terminal, railway, and subway services, while the sector of services related to engineering, architecture, geology, urban planning, construction, maintenance, cleaning, environment, sanitation, and the like, responded with the worst index. The model also showed that those who opt for the National Simples regime had, on average, a higher efficiency score compared to non opters.